Impact of ejecta morphology and composition on the electromagnetic signatures of neutron star mergers. Issue 3 (21st April 2018) - Wollaeger, Ryan T; Korobkin, Oleg; Fontes, Christopher J; Rosswog, Stephan K; Even, Wesley P; Fryer, Christopher L; Sollerman, Jesper; Hungerford, Aimee L; van Rossum, Daniel R; Wollaber, Allan B
ABSTRACT: The electromagnetic transients accompanying compact binary mergers (γ-ray bursts, afterglows and 'macronovae') are crucial to pinpoint the sky location of gravitational wave sources. Macronovae are caused by the radioactivity from freshly synthesized heavy elements, e.g. from dynamic ejecta and various types of winds. We study macronova signatures by using multidimensional radiative transfer calculations. We employ the radiative transfer code supernu and state-of-the-art LTE opacities for a few representative elements from the wind and dynamical ejecta (Cr, Pd, Se, Te, Br, Zr, Sm, Ce, Nd, U) to calculate synthetic light curves and spectra for a range of ejecta morphologies. The radioactive power of the resulting macronova is calculated with the detailed input of decay products. We assess the detection prospects for our most complex models, based on the portion of viewing angles that are sufficiently bright, at different cosmological redshifts ( z ). The brighter emission from the wind is unobscured by the lanthanides (or actinides) in some of the models, permitting non-zero detection probabilities for redshifts up to z  = 0.07. We also find that the nuclear mass model and the resulting radioactive heating rate are crucial for the detectability. While for the most pessimistic heating rate (from the finite range droplet model) no reasonable increase in the ejecta mass or velocity, or wind mass or velocity, can possibly make the light curves agree with the observed near-infrared excess after GRB130603B, a more optimistic heating rate (from the Duflo–Zuker model) leads to good agreement. We conclude that future reliable macronova observations would constrain nuclear heating rates, and consequently help constrain nuclear mass models.